The effects of e-beam radiation in the antioxidant potential of chestnuts (Castanea sativa Mill.) - Carocho, Márcio (2012)
Chestnut fruits (Castanea sativa Mill.) are widely consumed all over the world, and have been studied in terms of nutritional value and also for their antioxidant potential [1]. In Europe, Portugal is a leading producer of this nut, along with Italy, and the conservation of the chestnut’s properties is essential, especially for export [2]. Irradiation might be an alternative conservation method, since Methyl Bromide, a widely used fumigant, was prohibited as a conservation technique by the European Union in 2010 due to its toxicity for the operators and environment. The alternatives, hot water dip treatment among others, still present some disadvantages. Irradiation food treatment is considered an environment friendly technology and both safe to consumer and nutritionally adequate [3]. The present study reports the effect of e-beam radiation (doses of 0, 0.5, 1 and 3 kGy, being 0 the control, non-irradiated) on the antioxidant potential of Portuguese chestnuts, as an ongoing project with previous results for gamma radiation [2]. The antioxidant activity was evaluated through 2,2-diphenyl-1-pycrylhydrazyl (DPPH) free radical scavenging activity assay, reducing power by the Ferricyanide/Prussian blue assay, and lipid peroxidation inhibition by β-carotene/linoleate and thiobarbituric acid reactive substances (TBARS) assays. Total phenolics and flavonoids were performed by spectrophotometric assays. Irradiated samples seemed to preserve total phenolics content (but not flavonoids) and revealed higher antioxidant activity (lower EC50 values) than the control samples. The most indicated dose to maintain antioxidants content, and to increase antioxidant activity was 1 kGy.